The PKHs’ Implementation in Enhancing the Welfare Floating Houses in Makassar City - Syarifah Rafikah; Nika Nurdiana (Jurnal Ilmu Manajemen Profitability, 2025)
One of the government’s policies to address poverty is the Program Keluarga Harapan (PKH). The program aims to improve the socioeconomic, educational, and health conditions of poor communities. This study employed a descriptive qualitative research method, with data collected through observation and in-depth interviews. The findings indicate that the implementation of PKH in the Floating House community of the Fishermen Village in Tallo Subdistrict, Tallo District, Makassar City, has received support from various stakeholders, particularly the Tallo Subdistrict government. The recipients have shown considerable enthusiasm for the program. However, this research is urgent to evaluate the actual impact of PKH on improving the welfare of coastal communities with limited economic opportunities, education, and healthcare access. While the program has gained positive responses, challenges remain in ensuring its sustainability and effectiveness in breaking the cycle of poverty. Therefore, this study is essential to identify existing obstacles in program implementation and offer recommendations for enhancing its effectiveness. The findings are expected to contribute to policy development, ensuring that PKH and similar social assistance programs are better targeted and more impactful in reducing poverty, particularly among vulnerable fishing communities.